SITUATING ENGLISH SEGMENTAL AND SUPRASEGMENTAL FEATURES PROPORTIONALLY: A PROFILE OF INDONESIAN EFL STUDENTS - Fuad Abdullah; Lulita Lulita (Institut Pendidikan Indonesia Garut, 2018)
Recently, although teaching and learning English pronunciation has gained much attention from the linguists and TESOL practitioners, the students’ English pronunciation at the English Education Department of Siliwangi University may still remain under-researched. This study was aimed at scrutinizing how the students’ English pronunciation at the English Education Department of Siliwangi University is. Twenty six students participated in this study. The data were collected through reading aloud task. The data were analyzed with Wolcott’s data analysis procedures, namely description, analysis and interpretation (Wolcott as cited in Gibson & Brown, 2009:5). The findings indicated that the students presumably faced difficulties in producing not only suprasegmental but also segmental features. Hence, more emphasis should be addressed on the balanced proportion of teaching and learning the English segmental and suprasegmental features to attain intelligibility as the primary goal of teaching English pronunciation currently.